1999
DOI: 10.1007/s002140050517
|View full text |Cite
|
Sign up to set email alerts
|

Transition structures and exo/endo stereoselectivities of concerted [6 + 4] cycloadditions with density functional theory

Abstract: Density functional theory transition structures were located for three concerted [6 + 4] cycloaddition reactions involving cis-hexatriene and butadiene, cyclopentadiene and cycloheptatriene, and cyclopentadiene and tropone. Geometries, energies, and entropies were computed at the Becke3LYP/6-31G* level. The activation energy of the concerted [6 + 4] cycloaddition of hexatriene and butadiene is 33.3 kcal/mol, about 8 kcal/mol above the activation energy of the butadiene plus ethylene [4 + 2] cycloaddition. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…This interaction destroys the bilateral plane of symmetry in TS-1 and makes the exo -[6+4] highly asynchronous. By contrast, we previously showed that cyclopentadiene and cycloheptatriene, which lack this secondary interaction, react via a symmetrical and synchronous [6+4] TS. In a typical pericyclic ambimodal TS, the common bond among the reactions is significantly formed at ∼2 Å, and the competing partial bonds are around ∼3 Å …”
Section: Resultsmentioning
confidence: 93%
“…This interaction destroys the bilateral plane of symmetry in TS-1 and makes the exo -[6+4] highly asynchronous. By contrast, we previously showed that cyclopentadiene and cycloheptatriene, which lack this secondary interaction, react via a symmetrical and synchronous [6+4] TS. In a typical pericyclic ambimodal TS, the common bond among the reactions is significantly formed at ∼2 Å, and the competing partial bonds are around ∼3 Å …”
Section: Resultsmentioning
confidence: 93%
“…It was found that the [6+4] cycloaddition is a stepwise process (Figure S1 of the Supporting Information). The pericyclic processes, known for cyclopentadiene or dimethylfulvene as dienes , become stepwise, polar intermediate cycloadditions with the dienamines as 4π-reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal and entropic contributions to the free energies were also obtained from the vibrational frequency calculations, using the unscaled frequencies. All of the located transition states were confirmed to connect to reactants and products by intrinsic reaction coordinate (IRC) calculations. , For all diradical transition states and intermediates, a spin-projection scheme has been used to estimate energies of singlet diradical structures. However, the corresponding free energies are given without spin-correction because its effectiveness has not been completely demonstrated. ,, Calculations have been carried out both in the gas phase and considering solvent effects (toluene) with the PCM model. …”
Section: Methodsmentioning
confidence: 99%